KAPASITAS ADSORPSI BEBERAPA JENIS KULIT PISANG TERAKTIVASI NaOH SEBAGAI ADSORBEN LOGAM TIMBAL (Pb) - Purnama, Putu Eka; Sri Panca Dewi, I Gusti Ayu Kunti; Ratnayani, Ketut (Jurnal Kimia (Journal of Chemistry), 2015)
Adsorption capacity of various types of banana skin (green, kepok and susu) activated with NaOH as adsorbents for lead (Pb) has been studied. This research consisted of several steps included determination of the surface area of activated and unactivated adsorbents, equilibrium time, adsorption isotherms and adsorption capacity of adsorbents from green, kepok and susu banana skins activated with NaOH . The results showed that adsorbents from green, kepok and susu banana skin activated with NaOH had surface were of 36.2181 m 2 /g, 35.5531 m 2 /g and 35.8378 m 2 /g respectively. On the other hand, the surface area of unactivated adsorbents of green, kepok and susu banana skin were 35.3105 m 2 /g, 35.3199 m 2 /g, and 35.7928 m 2 /g respectively. Equilibrium time for green, kepok and susu banana skin adsorbents activated with NaOH  were 30; 30 and 90 minutes. Adsorption isotherms of adsorbents from green, kepok and susu banana skin activated with NaOH  were at concentration 100 ppm. Adsorption capacity of activated adsorbents from green banana, kepok banana and susu banana skin were 7.022 mg/g, 5.3078 mg/g and 6.6850 mg/g respectively.
Keywords: adsorption capacity, green banana, kepok banana, milk banana, lead (Pb)